Assessing and characterizing oilseed rape freezing injury based on MODIS and MERIS data - Bao, She; Jingfeng, Huang; Dongyan, Zhang; Linsheng, Huang (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: The oilseed rape growing in the lower reaches of Yangtze River in China belongs to winter varieties and suffers the risk of freezing injury. In this research, a typical freezing injury event occurred in Anhui Province was taken as a case study, the freezing damage degree of oilseed rape was assessed, and its development characteristics based on the vegetation metrics derived from MODIS and MERIS data were investigated. The oilseed rape was mapped according to the decline of greenness from bud stage to full-bloom period, with the phenological phases identified adopting time-series analyses. NDVI was more sensitive to freezing injury compared with other commonly used vegetation indices (VIs) calculated using MODIS bands, e.g., EVI, GNDVI and SAVI. The freezing damage degree employing the difference between post-freeze growth and the baseline level in adjacent damage-free growing seasons was determined. The remote sensing-derived damage levels were supported by their correlation with the cold accumulated temperatures at the county level. The performance of several remote sensing indicators of plant biophysical and biochemical parameters was also investigated, i.e., the photosynthetic rate, canopy water status, canopy chlorophyll content, leaf area index (LAI) and the red edge position (REP), in response to the advance of the freezing damage. It was found that the photosynthetic rate indicator—Photochemical Reflectance Index (PRI) responded strongly to freezing stress. Freezing injury caused canopy water loss, which could be detected though the magnitude was not very large. MERIS-LAI showed a slow and lagging response to low temperature and restored rapidly in the recovery phase; additionally, REP and the indicator of canopy chlorophyll content—MERIS Terrestrial Chlorophyll Index (MTCI), did not appear to be influenced by freezing injury. It was concluded that the physiological functions, canopy structure, and organic content metrics showed a descending order of vulnerabilities to freezing injury.Keywords: Brassica napus, oilseed rape, freezing injury, crop monitoring, MODIS, MERISDOI: 10.3965/j.ijabe.20171003.2721Citation: She B, Huang J F, Zhang D Y, Huang L S. Assessing and characterizing oilseed rape freezing injury based on MODIS and MERIS data. Int J Agric & Biol Eng, 2017; 10(3): 143–157.